GUN1 involvement in the redox changes occurring during biogenic retrograde signaling. (July 2022) - Fortunato, Stefania; Lasorella, Cecilia; Tadini, Luca; Jeran, Nicolaj; Vita, Federico; Pesaresi, Paolo; de Pinto, Maria Concetta
Abstract: Chloroplast biogenesis requires a tight communication between nucleus and plastids. By retrograde signals, plastids transmit information about their functional and developmental state to adjust nuclear gene expression, accordingly. GENOMES UNCOUPLED 1 (GUN1), a chloroplast-localized protein integrating several developmental and stress-related signals, is one of the main players of retrograde signaling. Here, we focused on the interplay between GUN1 and redox regulation during biogenic retrograde signaling, by investigating redox parameters in Arabidopsis wild type and gun1 seedlings. Our data highlight that during biogenic retrograde signaling superoxide anion (O2 - ) and hydrogen peroxide (H2 O2 ) play a different role in response to GUN1. Under physiological conditions, even in the absence of a visible phenotype, gun1 mutants show low activity of superoxide dismutase (SOD) and ascorbate peroxidase (APX), with an increase in O2 - accumulation and lipid peroxidation, suggesting that GUN1 indirectly protects chloroplasts from oxidative damage. In wild type seedlings, perturbation of chloroplast development with lincomycin causes H2 O2 accumulation, in parallel with the decrease of ROS-removal metabolites and enzymes. These redox changes do not take place in gun1 mutants which, in contrast, enhance SOD, APX and catalase activities. Our results indicate that in response to lincomycin, GUN1 is necessary for the H2 O2 -dependent oxidation of cellular environment, which might contribute to the redox-dependent plastid-to nucleus communication. Highlights: During chloroplast biogenesis, GUN1 is involved in the control of O2 - accumulation. In wild type seedlings, lincomycin induces hydrogen peroxide accumulation. In wild type seedlings, lincomycin reduces cellular antioxidant capability. GUN1 mediates the lincomycin-induced H2 O2 -dependent oxidation of cell environment. GUN1-dependent cellular oxidation signals plastid perturbations to the nucleus.